The Integrated E-LKPD Development with SQ4R Learning Strategy to Train Students’ Metacognition Ability - Hasna, Nisa Nur; Dewi, Novi Ratna (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research is stimulated by the low metacognitive ability of students in Indonesia. The real impact of students' low metacognitive ability is that they are unable to monitor themselves and do not know the nature of their learning goals. The use of the integrated E-LKPD (e-worksheet) with SQ4R learning strategies (Survey, Question, Read, Recite, Reflect, Review) has the potential to be an alternative choice to train students' metacognitive ability. This study aims to determine the validity of the product, and product characteristics as well as to train the metacognition ability’s profile of each student. This type of research is development research with the 4D model development. The integrated E-LKPD with SQ4R strategy has the characteristics; integrated with SQ4R strategy, train metacognitive abilities, attractive E-LKPD, flexible E-LKPD, interactive E-LKPD, and E-LKPD includes general requirements for LKPD. The results of the study prove that the integrated E-LKPD with the SQ4R strategy is valid with an average V index of 0.95 in the material aspect and 0.94 in the media aspect with the V table of 0.87. The results of the MAI questionnaire obtain a metacognitive profile of 85.25 with well-developed metacognition criteria. Thus, the developed E-LKPD has been tested to be valid and, therefore, can be used to train students' metacognitive ability.